2016
DOI: 10.1016/j.renene.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Study of the simultaneous effects of secondary flow and sediment erosion in Francis turbines

Abstract: a b s t r a c tSediment erosion of the hydropower turbine components is one of the key challenges due to the constituent of hard particles in the rivers of Himalayas and Andes. In the case of Francis turbines, previous studies show that the erosion is mostly observed around stay vanes, guide vanes and runner blades. Depending upon the type of flow phenomena in particular regions and operating conditions, the sediment particles having certain geometric and material properties create distinct erosion patterns on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 22 publications
(27 reference statements)
0
30
0
Order By: Relevance
“…However, due to the circumferential orientation of Figure 11. Cavitation and sediment erosion prone zones in Francis runner [5].…”
Section: Sedimentation Engineering 20mentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the circumferential orientation of Figure 11. Cavitation and sediment erosion prone zones in Francis runner [5].…”
Section: Sedimentation Engineering 20mentioning
confidence: 99%
“…A detailed investigation of the eroded components of these turbines has shown that turbines erode depending upon the particular types of flow phenomena in particular regions. It has been explained that the secondary flow and sediment erosion in turbines are simultaneous in nature [5], which means that one phenomenon aggravates another. In most of the cases, the condition gets worse because of the cavitation induced after the surfaces are eroded.…”
Section: Introductionmentioning
confidence: 99%
“…Because of sediment disintegration stream design changes, loss in effectiveness and vibration delivered, lastly breakdown of hydro turbine happen. Various research have been attempted to foresee the conduct and to decrease the impact of disintegration in hydro turbines, because of sediment [13][14][15][16][17][18][19][20].…”
Section: Small Hydro Powermentioning
confidence: 99%
“…However, due to the complexity of the structure of the double-suction centrifugal pump, the quantitative correlation of the mechanism of impeller blade wear is lack of systematic research. The morphology observation experiment method can locate the erosion wear form and damage degree of the blade surfaces after running for a period of time (Serrano et al 2018;Chitrakar et al 2016). Additionally, to optimize the design of doublesuction impeller and the pumping system, it is important to consider the influence of particles on the trajectories in the computational domain and identify the location and erosion rate density distribution on the impeller blades for sediment flows in pumps.…”
Section: Introductionmentioning
confidence: 99%